The complex trajectory method and dissipation in fission - Karpeshin, F. (2003)
Abstract The sensitivity of the muon attachment probabilities to the light fragments of prompt fission W l on the fission dynamics is discussed. It is shown that the final W l value consists of two contributions: one from the point of scission and a second from avoided crossing of the levels. The relative contribution from the prescission phase turns out to be higher for more asymmetric fission.